Effect Blanching Methods And Soaking Solution Sodium Bisulfit On The Physical And Chemical Characteristics Of Porang (Amorphophallus Muelleri Blume)Flour - Pardi, Lasmono; Prabowo , Sulistyo; Rohmah, Miftakhur; Marwati; Andriyani, Yulian (Universitas Dr Soetomo, 2024)
The porang plant belongs to the Arceae family which is a type of tuber plant. Porang tubers contain glucomannan which can be useful in the food and non-food industries. Porang tubers contain calcium oxalate which causes itching and can even harm health. Porang tubers also contain carotene, polyphenol oxidase,and tannins that can cause browning reactions. Different blanching methods (boiling and steaming) continued by soaking in different concentrations of sodium bisulfite (0.5%, 0.75%, 1.00%) were used in this study. The treatment of blanching and soaking with sodium bisulfite has an effect on the physical and chemical properties of porang flour. The higher concentration of soaking and increase ash content, water absorption capacity, glucomanan content, and improve color, yellowish white color and can reduce water content and calcium oxalate.